2016
DOI: 10.5371/hp.2016.28.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results of the Cephalomedullary Nail for the Femoral Intertrochanteric Fracture: Comparison between Non-experienced Surgeons and Experienced Surgeon

Abstract: PurposeCephalomedullary nail (CM nail) in the treatment of femoral intertrochanteric fractures is in the lime light in recent years. The purpose of this study is to compare surgical outcomes between experienced surgeon and non-experienced surgeons in respect of CM nail for femoral intertrochanteric fractures.Materials and MethodsThe 129 patients underwent CM nail for femoral intertrochanteric fracture more than six months of follow-up from April 2011 to March 2014 in Seoul Medical Center (Seoul, Korea) were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Longer antirotation screws increases the cutout risk because in this situation, the thinner screw assumes a load-bearing function. [5] Rethnam et al [13] Korkmaz et al [6] Menezes et al [15] Seo et al [10] Simmermacher et al [16] Our…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Longer antirotation screws increases the cutout risk because in this situation, the thinner screw assumes a load-bearing function. [5] Rethnam et al [13] Korkmaz et al [6] Menezes et al [15] Seo et al [10] Simmermacher et al [16] Our…”
Section: Discussionmentioning
confidence: 95%
“…Our results on implant related complications are in accordance with the existing literature on PFN related complications (Table 4). Previous studies have reported complication rates ranging from 4.5 -9.3%, re-operation rates of 3 -12%, and screw cutout rates of 1.2 -5.4% [5,10,11,15] . We had no cases of peri-implant fracture.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…30,31 Cephalo-medullary implants have shorter lever arm for the fixation device allowing lower potential for the fracture collapse and limb shortening when used for unstable trochanteric fractures. 21 Even the cephalo-medullary implants have been evolving over the last two decades. Screw proximal femoral nail was developed by AO/ASIF in 1996 to reduce difficulties faced in earlier intramedullary devices with design features like fluting of nail tip, additional anti-rotation screw and more proximal shifting of distal locking screw to enable gradual change in stiffness of nail construct.…”
Section: Discussionmentioning
confidence: 99%
“…19 The quality of the fracture reduction was quantified by the measurement of the postoperative fracture gap and the Garden Alignment Index. 20 The implant position in the femoral head was documented via the Cleveland zones 21,22 and the Tip Apex Distance (TAD). 18,23 The TAD was calculated by measuring the distance between the tip of the proximal implant (lag screw) to the apex of the femoral head on the AP and lateral X-ray after Baumgaertner's formula.…”
Section: Surgery and Postoperative Managementmentioning
confidence: 99%